DISCOVERY OF A DOOR IN THE POTOSI HUACA, MARANGA - Taira Custodio, Johnny (2014)
This article is about the archaeological discovery of a door found during the 2003 excavations in the mound complex 19 Potosi, this mound is part of the Maranga, under the Rimac valley. Consider important to the discovery of this element, as there are very few specimens (an example is the door of Pachacamac), and can give us important data to explain the use of the doors in the complex Maranga. The door was associated with a adobitos passageway that led to a quadrangular enclosure painted ocher-yellow, apparently, the door is part of a rite of sealing, with burning and burial of structure. In the present article provides the results of the analysis we perform, as well as a possible interpretation of architectural and social function of the doors during the final stages of the Lima culture (Maranga).